Monodisperse submicron core-shell structure low-temperature rare earth-based denitration catalyst as well as preparation method and application thereof

By using a monodispersed submicron core-shell structure low-temperature rare earth-based denitrification catalyst, and using iron tetraoxide to wrap the silver core and composite oxide active components, the problem of low efficiency of NOx catalyst under low temperature conditions in the waste incineration industry is solved, and efficient low-temperature denitrification effect is achieved, and environmentally friendly and low-cost advantages are achieved.

CN119733530AActive Publication Date: 2025-04-01NANJING TECH UNIV +2

Patent Information

Application Number
CN202510080101.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-19
Publication Date
2025-04-01
Estimated Expiration
2045-01-19

AI Technical Summary

Technical Problem

It is difficult to achieve the catalytic efficiency of NOx catalysts under low temperature conditions in the existing waste incineration industry to meet the standards.

Method used

A monodispersed submicron core-shell structure low-temperature rare earth-based denitrification catalyst is used. The catalyst consists of an iron tetraoxide-encapsulated silver core, an outer layer of composite oxide active components, a vanadium oxide cocatalyst, a polyacrylic acid in situ generator, a sodium sulfite light reducing agent and an oxalic acid morphology control agent, and is prepared by a combined method of in situ reduction-high temperature hydrothermal-impregnation loading.

Benefits of technology

Under low temperature conditions (90~300℃), the denitrition efficiency of the catalyst is higher than 90%. At the same time, the catalyst components are environmentally friendly, the preparation process is simple, and the cost is low, and it has strong application promotion value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005248356180000011
    Figure HDA0005248356180000011
  • Figure HDA0005248356180000012
    Figure HDA0005248356180000012
  • Figure HDA0005248356180000021
    Figure HDA0005248356180000021
Patent Text Reader

Abstract

The invention discloses a low-temperature rare-earth-based denitration catalyst with a monodisperse submicron core-shell structure and a preparation method and application thereof.The catalyst takes monodisperse ferroferric oxide wrapped silver as an inner core, takes a composite oxide of cerium dioxide and manganese oxide as an outer layer of an active component, takes vanadium oxide as a promoter and takes polyacrylic acid as an in-situ generating agent, and the low-temperature rare-earth-based denitration catalyst with the monodisperse submicron core-shell structure is prepared. Sodium sulfite is used as a light reducing agent, oxalic acid is used as a morphology control agent, and an in-situ reduction-high-temperature hydrothermal-impregnation loading combined method is adopted for preparation; on the basis of the mass of the inner core, the mass percentage of the active component outer layer is 5-10%, and the mass percentage of the cocatalyst is 1-5%. The catalyst synthesized by the method has the advantages of large specific surface area, sufficient exposure of active sites and the like, and can achieve the goal of ultralow emission of nitrogen oxides under the low-temperature flue gas working condition in the waste incineration industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of a monodisperse submicron core-shell structured low-temperature rare earth-based denitration catalyst, belonging to the field of industrial flue gas purification. Background Art

[0002] With the acceleration of urbanization, the output of domestic waste has increased year by year. Traditional landfill and stacking methods are gradually unable to meet environmental protection requirements. Waste incineration has gradually become one of the main methods for modern urban solid waste treatment. Although waste incineration can effectively reduce the volume of waste and save land resources, this process is also accompanied by certain environmental pollution risks, especially air pollution. During the waste incineration process, nitrogen oxides (NO x ) are atmospheric pollutants represented by these substances, which can cause acid rain and ozone pollution, seriously affecting human health and ecological safety.

[0003] In order to meet this challenge, many countries and regions have formulated strict waste incineration emission standards, striving to minimize the amount of pollutants emitted by the waste incineration industry. x The most important treatment technology is the selective catalytic reduction (SCR) method, which has been well applied in the thermal power industry. However, in the process of waste incineration, the flue gas temperature is usually below 300°C, and the catalytic efficiency of the SCR catalyst under low temperature conditions makes it difficult to achieve standard emissions of waste incineration flue gas pollutants.

[0004] In order to achieve effective NO x Control, there is an urgent need to develop denitrification catalysts that can work efficiently at lower temperatures (below 300°C). Therefore, the development of highly active low-temperature denitrification catalysts is one of the important directions of flue gas purification research in the waste incineration industry. Summary of the invention

[0005] The purpose of the present invention is to address the problems of catalytic activity of low-temperature denitration catalysts for flue gas in the existing waste incineration industry, and to propose a preparation method and application of a monodisperse submicron core-shell structured low-temperature rare earth-based denitration catalyst.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] A low-temperature rare earth-based denitration catalyst with a monodisperse submicron core-shell structure, comprising a core of monodisperse ferroferric oxide-wrapped silver, an outer layer of an active component of a composite oxide of cerium dioxide and manganese oxide, vanadium oxide as a co-catalyst, polyacrylic acid as an in-situ generating agent, sodium sulfite as a light reducing agent, and oxalic acid as a morphology controlling agent, and is prepared by an in-situ reduction-high-temperature hydrothermal-impregnation loading combined method; based on the mass of the core, the mass percentage of the active component outer layer is 1-10%, the mass percentage of the co-catalyst is 1-10%, the mass ratio of cerium dioxide to manganese oxide in the active component is 1:(0.1-5), and the mass ratio of ferroferric oxide to silver in the core is 1:(0.1-1).

[0008] As a preferred technical solution, in the above-mentioned monodisperse submicron core-shell structured low-temperature rare earth-based deNOx catalyst: based on the mass of the inner core, the mass percentage of the outer layer of the active component is 5-10%, the mass percentage of the co-catalyst is 1-5%, the mass ratio of cerium dioxide and manganese oxide in the active component is 1:(0.5-2), and the mass ratio of ferrosoferric oxide and silver in the inner core is 1:(0.1-0.2).

[0009] A method for preparing the above-mentioned catalyst, the method for preparing the catalyst is as follows:

[0010] (1) Preparation of FeO-encapsulated silver core by in-situ reduction-high temperature hydrothermal method

[0011] The paper is immersed in a polyacrylic acid solution and then taken out, and is dried at low temperature for later use; then the paper adsorbed with polyacrylic acid is immersed in a silver salt solution, and is dried at low temperature again and placed in a sodium borohydride solution for reaction, and after the reaction is completed, drying and first calcination are performed in sequence, and the powder obtained after calcination is washed to obtain monodisperse nano silver particles;

[0012] The monodisperse nanosilver particles, iron salt, sodium sulfite, oxalic acid and deionized water are uniformly mixed, and then placed in a hydrothermal reactor for high-temperature hydrothermal reaction. After the reaction is completed, the mixture is filtered, dried and calcined for a second time to obtain a silver core wrapped with ferroferric oxide;

[0013] (2) Preparation of catalyst by impregnation loading method

[0014] Weigh cerium salt, manganese salt, vanadium salt and deionized water and mix them evenly to obtain a composite precursor solution, then place the ferroferric oxide-wrapped silver core obtained in step (1) into the composite precursor solution, dry at low temperature and then calcine at high temperature to obtain a monodisperse submicron core-shell structured low-temperature rare earth-based denitrification catalyst.

[0015] In the above preparation method: in step (1), the concentration of the polyacrylic acid solution is 1 to 10 wt %; the concentration of the silver salt solution is 1 to 15 wt %; the concentration of the sodium borohydride solution is 1 to 10 wt %;

[0016] Preferably, the concentration of the polyacrylic acid solution is 2-6 wt %; the concentration of the silver salt solution is 5-10 wt %; and the concentration of the sodium borohydride solution is 1-5 wt %.

[0017] In the above preparation method: the reaction time in step (1) is 30 to 60 minutes; the low-temperature drying temperature is 25 to 35° C., and the low-temperature drying time is 20 to 24 hours.

[0018] In the above preparation method: the drying temperature in step (1) is 50-60°C, the drying time is 2-4h, the first roasting temperature is 500-600°C, and the first roasting time is 2-3h.

[0019] In the above preparation method: the temperature of the high-temperature hydrothermal reaction in step (1) is 140-160°C, and the time of the high-temperature hydrothermal reaction is 3-6 hours; the temperature of the drying is 80-100°C, and the time of the drying is 3-6 hours; the temperature of the second roasting is 400-500°C, and the time of the second roasting is 2-4 hours.

[0020] In the above preparation method: in step (2), the cerium salt is cerium nitrate hexahydrate or cerium chloride, the manganese salt is manganese nitrate hexahydrate or manganese chloride, and the vanadium salt is ammonium metavanadate; the low-temperature drying temperature is 30-40°C, and the low-temperature drying time is 24-48h; the high-temperature roasting temperature is 500-600°C, and the high-temperature roasting time is 2-4h.

[0021] In the technical solution of the present invention, the catalyst is used in low-temperature denitrification in the waste incineration industry.

[0022] In the technical scheme of the present invention, further, polyacrylic acid and deionized water are mixed evenly to obtain a polyacrylic acid solution, and then paper is immersed in the polyacrylic acid solution and taken out, and is dried at low temperature for standby use; then silver salt and deionized water are mixed evenly to obtain a silver salt solution, and the paper adsorbed with polyacrylic acid is immersed in the silver salt solution, and is dried at low temperature and placed in a sodium borohydride solution for reaction, and is dried after the reaction is completed and placed in a muffle furnace for high-temperature roasting, and then the powder obtained after roasting is placed in a dilute hydrochloric acid solution and a sodium hydroxide solution for acid washing and alkali washing respectively, and then washed with deionized water to obtain monodisperse nano silver particles; monodisperse nano silver particles, iron salt, sodium sulfite, oxalic acid and deionized water are mixed evenly, and then placed in a hydrothermal reactor for high-temperature hydrothermal reaction, and after the reaction is completed, the paper is filtered, dried and roasted twice to obtain a silver core wrapped with ferroferric oxide; the dilute hydrochloric acid solution is a hydrochloric acid solution with a mass fraction of 5-10%, and the sodium hydroxide solution is a sodium hydroxide solution with a mass fraction of 10-20%, and the mass ratio of the dilute hydrochloric acid solution / sodium hydroxide solution to the roasted powder is 1: (30-40).

[0023] The experimental conditions for evaluating the activity of the catalyst of the present invention are as follows: 1 mL of a 20-40 mesh catalyst is taken and poured into a quartz tube with an inner diameter of 6 mm, fixed with quartz wool and wire mesh, and the quartz tube is placed in a tubular furnace, and the actual temperature of the catalytic reaction is adjusted by controlling the heating temperature of the tubular furnace. Intake gas components: NO (500 ppm), NH3 (500 ppm), O2 (11 vol.%), H2O (5 vol.%), and the rest are N2, the total gas flow rate is 500 mL / min, the temperature is controlled at 90-300°C, and it stays stable for 30 minutes every 30°C. The NO concentration is measured using a Laoying 3021 portable carbon emission monitor, and the catalyst denitrification efficiency is higher than 90% in the temperature range of 180-300°C.

[0024] Beneficial effects:

[0025] (1) The present invention uses polyacrylic acid to pretreat A4 paper, which can not only make the surface of A4 paper have more carboxyl groups, but also reduce the size of the confined structure formed by the interlacing of its fibers, thereby facilitating the adsorption and fixation of the silver salt solution, and then uses sodium borohydride solution to in-situ reduce the silver salt solution to prepare monodisperse nanosilver particles, and then uses roasting, acid washing and alkali washing to remove the paper to obtain high-purity monodisperse nanosilver particles, and finally uses the nanosilver particles and iron salt to thermally react to generate the submicron core of the ferroferric oxide-coated silver nanoparticles, wherein the iron salt is reduced by sodium sulfite, and oxalic acid is used as a morphology control agent to stably grow the ferroferric oxide-coated nanosilver particles;

[0026] (2) The present invention utilizes three composite oxides, namely, cerium oxide, manganese oxide and vanadium oxide, which have excellent redox properties as active components and co-catalysts, which can ensure the excellent low-temperature reduction activity of the catalyst. In addition, the silver and ferroferric oxide in the inner core not only have good electron transport properties and promote the improvement of activity, but also can be easily recovered and reused by utilizing the magnetism of ferroferric oxide when the catalyst is swept by ash in the flue gas in actual engineering, thereby ensuring that the catalyst is not prone to secondary pollution.

[0027] Therefore, the catalyst prepared by the present invention not only has excellent low-temperature flue gas denitrification performance, but also the catalyst component is environmentally friendly, has a simple preparation process, low cost, high cost performance, and has strong application and promotion value. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 TEM image of the catalyst prepared in Example 1;

[0029] Figure 2 TEM image of the catalyst prepared in Comparative Example 1;

[0030] Figure 3 This is a graph showing the NO removal performance of the catalysts prepared in Examples 1-3 and Comparative Examples 1-2. DETAILED DESCRIPTION

[0031] The present invention is further described below in conjunction with examples. The examples are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operating processes are given, but the protection scope of the present invention is not limited to the following examples.

[0032] Example 1

[0033] (1) Preparation of FeO-encapsulated silver core by in-situ reduction-high temperature hydrothermal method

[0034] 1g of polyacrylic acid and 20g of deionized water were mixed evenly to prepare a polyacrylic acid solution, and then 70g of paper was immersed in the polyacrylic acid solution and taken out, and dried at 30°C for 24h before use; then 1g of silver nitrate and 10g of deionized water were mixed evenly to prepare a silver salt solution, and the paper adsorbed with polyacrylic acid was immersed in the silver salt solution and dried at 30°C for 24h before use; 1g of sodium borohydride was dissolved in 30ml of deionized water to prepare a sodium borohydride solution, and the paper adsorbed with silver salt was placed in the solution to react for 30min, and after the reaction was completed, it was dried at 50°C for 2h and placed in a muffle furnace at 500°C. The powder obtained after calcination is then placed in 30g of 5% by mass dilute hydrochloric acid solution and 30g of 10% by mass sodium hydroxide solution for acid washing and alkali washing, and then washed with deionized water to obtain monodisperse nanosilver particles; 0.5g of monodisperse nanosilver particles, 26.17g of ferric nitrate nonahydrate, 0.25g of sodium sulfite, 1.5g of oxalic acid and 20ml of deionized water are mixed evenly, and then placed in a hydrothermal reactor for high temperature hydrothermal reaction at 140°C for 3h, after the reaction is completed, it is filtered and dried at 80°C for 3h and then secondary roasted at 400°C for 2h to obtain a silver core wrapped with ferroferric oxide;

[0035] (2) Preparation of catalyst by impregnation loading method

[0036] Weigh 0.084 g of cerium nitrate hexahydrate, 0.055 g of manganese nitrate hexahydrate, 0.013 g of ammonium metavanadate, and 2.6 ml of deionized water, mix them evenly to obtain a composite precursor solution, then place 1 g of the ferroferric oxide-coated silver core obtained in step (1) into the composite precursor solution, dry at 30° C. for 24 h, and then calcine at 500° C. for 2 h to obtain a monodisperse submicron core-shell structured low-temperature rare earth-based denitration catalyst;

[0037] Based on the mass of the inner core, the mass percentage of the outer layer of the active component is 5%, the mass percentage of the co-catalyst is 1%, the mass ratio of cerium dioxide to manganese oxide in the active component is 1:0.5, and the mass ratio of ferrosoferric oxide to silver in the inner core is 1:0.1;

[0038] (3) Catalytic activity test

[0039] Take 1mL of 20-40 mesh catalyst, pour it into a quartz tube with an inner diameter of 6mm, fix it with quartz wool and wire mesh, put the quartz tube in a tube furnace, and adjust the actual temperature of the catalytic reaction by controlling the heating temperature of the tube furnace. Intake components: NO (500ppm), NH3 (500ppm), O2 (11vol.%), the rest are N2, the total gas flow is 500mL / min, the temperature is controlled at 90-300℃, stay stable for 30min every 30℃, use Laoying 3021 portable carbon emission monitor to measure NO concentration, and the catalyst denitrification efficiency is higher than 90% in the temperature range of 150-300℃.

[0040] Example 2

[0041] (1) Preparation of FeO-encapsulated silver core by in-situ reduction-high temperature hydrothermal method

[0042] 1g of polyacrylic acid and 30g of deionized water were mixed evenly to prepare a polyacrylic acid solution, and then 75g of paper was immersed in the polyacrylic acid solution and taken out, and dried at 40°C for 36h before use; then 1g of silver nitrate and 15g of deionized water were mixed evenly to prepare a silver salt solution, and the paper adsorbed with polyacrylic acid was immersed in the silver salt solution and dried at 40°C for 36h before use; 1g of sodium borohydride was dissolved in 40ml of deionized water to prepare a sodium borohydride solution, and the paper adsorbed with silver salt was placed in the solution to react for 45min, and after the reaction was completed, it was dried at 55°C for 3h and placed in a muffle furnace to bake at 550°C calcining for 2.5h, and then placing the powder obtained after calcination in 35g of 8% by mass dilute hydrochloric acid solution and 35g of 15% by mass sodium hydroxide solution for acid washing and alkali washing, and then washing with deionized water to obtain monodisperse nanosilver particles; 0.7g of monodisperse nanosilver particles, 12.26g of ferric chloride hexahydrate, 0.5g of sodium sulfite, 2.8g of oxalic acid and 35ml of deionized water are mixed evenly, and then placed in a hydrothermal reactor for high temperature hydrothermal reaction at 150°C for 4.5h, after the reaction is completed, filtering and drying at 90°C for 5h and secondary calcining at 450°C for 3h to obtain a silver core wrapped with ferroferric oxide;

[0043] (2) Preparation of catalyst by impregnation loading method

[0044] Weigh 0.051 g of cerium chloride, 0.050 g of manganese chloride, 0.039 g of ammonium metavanadate, and 2.04 ml of deionized water and mix them evenly to obtain a composite precursor solution, then place 1 g of the ferroferric oxide-coated silver core obtained in step (1) into the composite precursor solution, dry at 30° C. for 36 h, and then calcine at 500° C. for 3 h to obtain a monodisperse submicron core-shell structured low-temperature rare earth-based denitration catalyst;

[0045] Based on the mass of the inner core, the mass percentage of the outer layer of the active component is 7%, the mass percentage of the co-catalyst is 3%, the mass ratio of cerium dioxide to manganese oxide in the active component is 1:1, and the mass ratio of ferrosoferric oxide to silver in the inner core is 1:0.15;

[0046] (3) Catalytic activity test

[0047] Take 1mL of 20-40 mesh catalyst, pour it into a quartz tube with an inner diameter of 6mm, fix it with quartz wool and wire mesh, put the quartz tube in a tube furnace, and adjust the actual temperature of the catalytic reaction by controlling the heating temperature of the tube furnace. Intake components: NO (500ppm), NH3 (500ppm), O2 (11vol.%), the rest are N2, the total gas flow is 500mL / min, the temperature is controlled at 90-300℃, stay stable for 30min every 30℃, use Laoying 3021 portable carbon emission monitor to measure NO concentration, and the catalyst denitrification efficiency is higher than 90% in the temperature range of 150-300℃.

[0048] Example 3

[0049] (1) Preparation of FeO-encapsulated silver core by in-situ reduction-high temperature hydrothermal method

[0050] 1g of polyacrylic acid and 30g of deionized water were mixed evenly to prepare a polyacrylic acid solution, and then 80g of paper was immersed in the polyacrylic acid solution and taken out, and dried at 40°C for 48h before use; then 1g of silver nitrate and 20g of deionized water were mixed evenly to prepare a silver salt solution, and the paper adsorbed with polyacrylic acid was immersed in the silver salt solution and dried at 40°C for 48h before use; 1g of sodium borohydride was dissolved in 50ml of deionized water to prepare a sodium borohydride solution, and the paper adsorbed with silver salt was placed in the solution to react for 60min, and after the reaction was completed, it was dried at 60°C for 4h and placed in a muffle furnace at 600°C. The powder obtained after calcination is then placed in 40g of 10% by mass dilute hydrochloric acid solution and 40g of 20% by mass sodium hydroxide solution for acid washing and alkali washing, and then washed with deionized water to obtain monodisperse nanosilver particles; 0.5g of monodisperse nanosilver particles, 13.1g of ferric nitrate nonahydrate, 0.5g of sodium sulfite, 2.5g of oxalic acid and 30ml of deionized water are mixed evenly, and then placed in a hydrothermal reactor for high temperature hydrothermal reaction at 140°C for 3h, after the reaction is completed, it is filtered and dried at 80°C for 3h and then secondary roasted at 400°C for 2h to obtain a silver core wrapped with ferroferric oxide;

[0051] (2) Preparation of catalyst by impregnation loading method

[0052] Weigh 0.085 g of cerium nitrate hexahydrate, 0.22 g of manganese nitrate hexahydrate, 0.065 g of ammonium metavanadate, and 4.25 ml of deionized water, mix them evenly to obtain a composite precursor solution, then place 1 g of the ferroferric oxide-coated silver core obtained in step (1) into the composite precursor solution, dry at 30° C. for 24 h, and then calcine at 500° C. for 2 h to obtain a monodisperse submicron core-shell structured low-temperature rare earth-based denitration catalyst;

[0053] Based on the mass of the inner core, the mass percentage of the outer layer of the active component is 10%, the mass percentage of the co-catalyst is 5%, the mass ratio of cerium dioxide to manganese oxide in the active component is 1:2, and the mass ratio of ferrosoferric oxide to silver in the inner core is 1:0.2;

[0054] (3) Catalytic activity test

[0055] Take 1mL of 20-40 mesh catalyst, pour it into a quartz tube with an inner diameter of 6mm, fix it with quartz wool and wire mesh, put the quartz tube in a tube furnace, and adjust the actual temperature of the catalytic reaction by controlling the heating temperature of the tube furnace. Intake components: NO (500ppm), NH3 (500ppm), O2 (11vol.%), the rest are N2, the total gas flow is 500mL / min, the temperature is controlled at 90-300℃, stay stable for 30min every 30℃, use Laoying 3021 portable carbon emission monitor to measure NO concentration, and the catalyst denitrification efficiency is higher than 90% in the temperature range of 150-300℃.

[0056] Comparative Example 1

[0057] (1) Preparation of FeO-encapsulated silver core by in-situ reduction-high temperature hydrothermal method

[0058] Except that A4 paper was not added during the preparation of the ferroferric oxide-wrapped silver core, other conditions were the same as those in Example 1;

[0059] (2) Catalytic activity test

[0060] Take 1mL of 20-40 mesh catalyst, pour it into a quartz tube with an inner diameter of 6mm, fix it with quartz wool and wire mesh, put the quartz tube in a tubular furnace, and adjust the actual temperature of the catalytic reaction by controlling the heating temperature of the tubular furnace. Intake components: NO (500ppm), NH3 (500ppm), O2 (11vol.%), the rest are N2, the total gas flow rate is 500mL / min, the temperature is controlled at 90-300℃, stay stable for 30min every 30℃, use Laoying 3021 portable carbon emission monitor to measure NO concentration, and the denitrification efficiency is 35.9% at 150℃;

[0061] (3) Contrast effect

[0062] Compared with Example 1, no A4 paper was added in the catalyst preparation step (1), and the silver salt was not adsorbed and fixed on the paper fibers. It agglomerated during sodium borohydride reduction, which resulted in the formation of monodisperse submicron particles when the ferroferric oxide was hydrothermally coated on the silver particles. The catalyst prepared at this time was agglomerated particles ( Figure 2 ), so the active sites of the prepared catalyst are greatly reduced, resulting in a decrease in the low-temperature catalytic activity of the catalyst.

[0063] Comparative Example 2

[0064] (1) Preparation of FeO-encapsulated silver core by in-situ reduction-high temperature hydrothermal method

[0065] Except that oxalic acid was not added during the preparation of the ferroferric oxide-coated silver core, other conditions were the same as those in Example 2; (2) Catalytic Activity Test

[0066] Take 1mL of 20-40 mesh catalyst, pour it into a quartz tube with an inner diameter of 6mm, fix it with quartz wool and wire mesh, put the quartz tube in a tubular furnace, and adjust the actual temperature of the catalytic reaction by controlling the heating temperature of the tubular furnace. Intake components: NO (500ppm), NH3 (500ppm), O2 (11vol.%), the rest are N2, the total gas flow rate is 500mL / min, the temperature is controlled at 90-300℃, stay stable for 30min every 30℃, use Laoying 3021 portable carbon emission monitor to measure NO concentration, and the denitrification efficiency at 150℃ is 39.8%;

[0067] (3) Contrast effect

[0068] Compared with Example 1, oxalic acid, a morphology control agent, was not added in the catalyst preparation step (1). Therefore, a core-shell structure with silver as the inner core encapsulated by ferroferric oxide could not be completely formed during the hydrothermal reaction of the monodisperse nanosilver particles and the iron salt. Under the condition of uneven morphology distribution, the loading of active components was uneven, thereby reducing the low-temperature catalytic activity of the catalyst.

Claims

1. A monodisperse submicron core-shell structured low-temperature rare earth-based denitration catalyst, characterized in that: The catalyst has a monodispersed ferroferric oxide-wrapped silver as an inner core, a composite oxide of cerium dioxide and manganese oxide as an outer layer of an active component, vanadium oxide as a co-catalyst, polyacrylic acid as an in-situ generating agent, sodium sulfite as a light reducing agent, and oxalic acid as a morphology controlling agent. The catalyst is prepared by an in-situ reduction-high-temperature hydrothermal-impregnation loading combined method. Based on the mass of the inner core, the mass percentage of the active component outer layer is 1-10%, the mass percentage of the co-catalyst is 1-10%, the mass ratio of cerium dioxide to manganese oxide in the active component is 1:(0.1-5), and the mass ratio of ferroferric oxide to silver in the inner core is 1:(0.1-1).

2. The monodisperse submicron core-shell structure low-temperature rare earth-based denitration catalyst according to claim 1, characterized in that: Based on the mass of the inner core, the mass percentage of the outer layer of the active component is 5-10%, the mass percentage of the co-catalyst is 1-5%, the mass ratio of cerium dioxide and manganese oxide in the active component is 1:(0.5-2), and the mass ratio of ferrosoferric oxide and silver in the inner core is 1:(0.1-0.2).

3. A method for preparing the catalyst according to claim 1, characterized in that: The preparation method of the catalyst is as follows: (1) Preparation of FeO-encapsulated silver core by in-situ reduction-high temperature hydrothermal method The paper is immersed in a polyacrylic acid solution and then taken out, and is dried at low temperature for later use; then the paper adsorbed with polyacrylic acid is immersed in a silver salt solution, and is dried at low temperature again and placed in a sodium borohydride solution for reaction, and after the reaction is completed, drying and first calcination are performed in sequence, and the powder obtained after calcination is washed to obtain monodisperse nano silver particles; The monodisperse nanosilver particles, iron salt, sodium sulfite, oxalic acid and deionized water are uniformly mixed, and then placed in a hydrothermal reactor for high-temperature hydrothermal reaction. After the reaction is completed, the mixture is filtered, dried and calcined for a second time to obtain a silver core wrapped with ferroferric oxide; (2) Preparation of catalyst by impregnation loading method Weigh cerium salt, manganese salt, vanadium salt and deionized water and mix them evenly to obtain a composite precursor solution, then place the ferroferric oxide-wrapped silver core obtained in step (1) into the composite precursor solution, dry at low temperature and then calcine at high temperature to obtain a monodisperse submicron core-shell structured low-temperature rare earth-based denitrification catalyst.

4. The preparation method according to claim 3, characterized in that: In step (1), the concentration of the polyacrylic acid solution is 1-10wt%; the concentration of the silver salt solution is 1-15wt%; the concentration of the sodium borohydride solution is 1-10wt%; preferably, the concentration of the polyacrylic acid solution is 2-6wt%; the concentration of the silver salt solution is 5-10wt%; and the concentration of the sodium borohydride solution is 1-5wt%.

5. The preparation method according to claim 3, characterized in that: The reaction time in step (1) is 30 to 60 minutes; the low-temperature drying temperature is 25 to 35° C., and the low-temperature drying time is 20 to 24 hours.

6. The preparation method according to claim 3, characterized in that: The drying temperature in step (1) is 50-60° C., the drying time is 2-4 hours, the first roasting temperature is 500-600° C., and the first roasting time is 2-3 hours.

7. The preparation method according to claim 3, characterized in that: In step (1), the temperature of the high-temperature hydrothermal reaction is 140-160° C., and the time of the high-temperature hydrothermal reaction is 3-6 hours; the temperature of the drying is 80-100° C., and the time of the drying is 3-6 hours; the temperature of the second roasting is 400-500° C., and the time of the second roasting is 2-4 hours.

8. The preparation method according to claim 3, characterized in that: In step (2), the cerium salt is cerium nitrate hexahydrate or cerium chloride, the manganese salt is manganese nitrate hexahydrate or manganese chloride, and the vanadium salt is ammonium metavanadate; the low-temperature drying temperature is 30-40° C., and the low-temperature drying time is 24-48 hours; the high-temperature roasting temperature is 500-600° C., and the high-temperature roasting time is 2-4 hours.

9. Use of the catalyst according to claim 1 in low-temperature denitrification in the waste incineration industry.

Citation Information

Patent Citations

  • Low-temperature denitration catalyst with core-shell structure and preparation method of low-temperature denitration catalyst

    CN108404930A

  • Preparation method of core-shell structure Fe2O3-CeO2 / (Al@C) high-temperature composite phase-change heat accumulation oxygen carrier

    CN109054756A

  • A method for preparing a carbon-coated Fe3N and a composite magnetic nanoparticle thereof

    CN109215913A

  • Method for preparing Ag / TiO2 nano-particles with core-shell structure at normal temperature and application

    CN112058260A

  • Manganese-cerium modified high-iron fly ash adsorbent for flue gas denitrification, and preparation method thereof

    CN112316900A

Cited By

  • Core-shell type low-temperature water-sulfur poisoning-resistant denitration catalyst as well as preparation method and application thereof

    CN121551019A